A solvent-free polyurea coating and its preparation method and application

By using solvent-free polyurea coating, which consists of components such as polyaspartate resin, aminosilane resin and polyisocyanate, the problem of existing coatings not having heat resistance under high temperature conditions is solved, and the excellent performance and long-term use of the coatings in high temperature environments are achieved.

CN117126588BActive Publication Date: 2025-04-29LIAONING XINFENG IND CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202311215986.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-04-29
Estimated Expiration
2043-09-20

AI Technical Summary

Technical Problem

Existing paints do not have long-term heat resistance under high temperature conditions and cannot meet the corrosion protection requirements of above-ground pipelines in high temperature areas such as the Middle East.

Method used

Solvent-free polyurea coating is used, which consists of component A and component B. Component A includes polyaspartate resin, aminosilane resin and pigment. Component B includes polyisocyanate, epoxy silicone resin and filler. The two components are mixed in volume ratio 1:1 to form a coating with high crosslinking density.

Benefits of technology

This solvent-free polyurea coating has excellent high temperature resistance, corrosion resistance, wear resistance and weather resistance, and can maintain adhesion and performance in high temperature environments to meet pipeline protection needs in the Middle East and other regions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_4
    Figure SMS_4
  • Figure SMS_7
    Figure SMS_7
  • Figure SMS_8
    Figure SMS_8
Patent Text Reader

Abstract

The present invention relates to a solvent-free polyurea coating, the coating comprises an A component and a B component, the A and B components are prepared separately, the raw material formula of the A component comprises by mass: 32.04 parts of polyaspartic acid ester resin, 2.12-3.92 parts of aminosilane resin, 3.64-3.89 parts of auxiliary agents and 8.5-12.3 parts of pigment; the raw material formula of the B component comprises by mass: 22.24 or 22.70 parts of polyisocyanate, 5.3-10.2 parts of epoxy silicone resin, 2.6-2.79 parts of auxiliary agents, 6-8.5 parts of rust-proof pigments and 20.17-22 parts of fillers; the volume ratio of the A component to the B component is 1: 1. The present invention adds aminosilane resin to the polyaspartic acid ester component, adds epoxysilane resin to the polyisocyanate component, and forms a reaction system with each other to form a polyurea coating with a higher crosslinking density.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to a solvent-free polyurea coating and a preparation method and application thereof. Background Art

[0002] Steel pipelines are a common means of transporting water, gas, oil, etc. over long distances. Therefore, pipeline protection is particularly important. At present, there are various types of external anti-corrosion coatings for underground steel pipelines, and the more commonly used ones are 3PE or 3PP, epoxy coatings, and polyurea coatings. Among them, 3PE or 3PP cannot be used for a long time at temperatures above 70°C, and even 3PP cannot be used at temperatures above 90°C. Excessively high operating temperatures will reduce the bonding strength between layers and cause the anti-corrosion coating to fail prematurely. The solvent-free epoxy coatings and polyurea coatings used for underground pipelines basically do not have good weather resistance.

[0003] The existing weather-resistant coating for above-ground pipelines basically adopts zinc-rich primer + epoxy intermediate paint + aliphatic polyurea (polyurethane) topcoat to achieve long-term corrosion protection, but such construction process is complicated, and a certain interval time is required between each layer, which does not meet the requirements of large-scale pipeline production. Especially for the Middle East, especially in summer, the surface temperature of the pipeline under sunlight can reach above 90°C, which puts higher requirements on the high temperature resistance of the coating. If the high temperature resistance of the coating is not good, it is very easy to cause the coating to blister and fail.

[0004] Aspartate-based polyurea coating compositions with long-term weathering resistance are well known in the art. For example, EP0403921 describes a coating composition containing an adhesive, which is based on a polyisocyanate component and an isocyanate-reactive component containing a specific secondary polyamine. These secondary polyamines are also called polyaspartic acid esters, which are reaction products based on primary polyamines and diesters of maleic acid and / or fumaric acid.

[0005] The biggest disadvantages of the above-mentioned aspartic acid ester polyurea-based coating combination, especially the solvent-free polyaspartic acid ester polyurea coating, are: fast curing speed, strong coating cohesion, and difficulty in meeting the requirements for adhesion to the substrate or interlayer adhesion.

[0006] Polyisocyanate mixtures comprising alkoxysilane groups have been known in the art for quite some time for improving the adhesion, chemical resistance or scratch resistance of coatings.

[0007] For example, WO 03054049 describes isocyanate-functional silanes as adhesion promoters for polyurethane hot melt adhesives, which are prepared from low-monomer aliphatic or alicyclic polyisocyanates and secondary aminopropyltrimethoxysilane.

[0008] CN115820099 describes a polyaspartic acid ester coating composition using a silane-modified HDI trimer as an isocyanate component for improving the adhesion between the coating and the metal.

[0009] WO02058569 describes reaction products of aliphatic or cycloaliphatic polyisocyanates with insufficient amounts of alkoxysilane-functional aspartic acid esters or secondary aminoalkylsilanes as crosslinker components for two-component polyurethane primers.

[0010] A common property of all these polyisocyanate mixtures containing silane groups is that they are prepared by partial reaction of unmodified polyisocyanates or polyisocyanate prepolymers with organofunctional silanes containing isocyanate-reactive groups, examples of which are mercapto-functional silanes, primary aminoalkylsilanes, secondary N-alkyl-substituted aminoalkylsilanes or alkoxysilane-functional aspartates.

[0011] However, such modification inevitably reduces the isocyanate functionality relative to the polyisocyanate initially used, and the impact of this reduction increases with the increase of the silane content in the reaction product, thereby reducing the crosslinking density of the coating and affecting the corrosion resistance of the coating.

[0012] CN102030883 discloses a high-functionality isocyanate containing allophanate and silane groups, which is produced by a ring-opening reaction of aminosilane (aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane) with cyclic carbonate and / or lactone (preferably ethylene carbonate, propylene carbonate), and then reacting with excess isocyanate to produce an allophanate polyisocyanate prepolymer with silane groups. Since this technology is a high-functionality isocyanate prepolymer, it does not affect the performance of the coating and can improve the bonding performance, but the process is very complicated.

[0013] CN1117934200 discloses a modified solvent-based polyaspartic acid ester polyurea coating. The invention introduces silicone units and epoxy units into polyaspartic acid ester to improve the low-temperature flexibility of the coating and increase the bonding strength of the polyurea coating. This technology uses silicone monomers to thermally graft polyaspartic acid ester resins during the synthesis of polyaspartic acid esters to obtain silicone-modified polyaspartic acid esters. The epoxy units introduced by this technology are bisphenol A type epoxy resins. The introduction of such substances will reduce the weather resistance of the coating. .

[0014] The above two technologies have complex overall preparation processes, high requirements for industrial equipment, and the hot splicing synthesis process is not very controllable. The overall preparation threshold is high and the application prospects are insufficient.

[0015] The cold blending of silicone resin into polyaspartic acid resin coating has been known in the art for quite a long time. The silicone resin is basically used as a coupling agent to improve the adhesion and other properties of the coating.

[0016] For example: CN105008424 discloses a solvent (large amount of solvent) type two-component coating composition, which includes two components: the polyaspartic acid ester component is polyaspartic acid ester, n-butyl acetate solvent, and hydroxy acrylic resin; the polyisocyanate crosslinking agent component containing an NCO group is: a polyisocyanate containing an NCO group, an epoxy silane coupling agent (A187), and n-butyl acetate solvent. The coating composition is mainly used to improve the moisture resistance and adhesion of the coating.

[0017] CN113122129 discloses a low-viscosity solvent-free polyurea coating, which is used to solve the problem of high VOC emission in existing polyaspartic acid ester polyurea coatings. Its A component adopts cold blending of epoxy polysiloxane resin and polyaspartic acid ester resin. The inventor believes that the addition of epoxy polysiloxane resin can be used as a diluent of the system to reduce the viscosity of the system and participate in the reaction. This epoxy silane can participate in the reaction, that is, the reaction with the polyaspartic acid ester of the A component. According to the comparative experiment, the NH-group of part of the aspartic acid ester will be consumed during the storage and stacking process of the coating A component, and the NCO group prepared in proportion with the B component cannot be completely reacted, causing the coating performance to change, and at the same time causing the viscosity of the A component to increase. It does not show the characteristic of reducing the viscosity of the system described in the present invention, which is not conducive to construction.

[0018] The existing polyaspartic acid ester polyurea technical solutions are basically to solve the adhesion between the coating and the substrate, the interlayer adhesion, low temperature flexibility, VOC content and other technical solutions. Although it has excellent weather resistance, it does not have long-term heat resistance and cannot meet the anti-corrosion requirements of aboveground pipelines in high-temperature areas such as the Middle East. Therefore, the research of a solvent-free polyurea coating that can be sprayed on an assembly line with high temperature resistance, excellent corrosion resistance, wear resistance, and weather resistance is the focus and difficulty of the research on coatings for the outer wall of aboveground pipelines in high-temperature areas such as the Middle East under high-temperature environments. Summary of the invention

[0019] The purpose of the present invention is to provide a solvent-free polyurea coating that can be sprayed on an assembly line and has high temperature resistance, excellent corrosion resistance, wear resistance and weather resistance, so as to solve the problem that the existing coating does not have long-term heat resistance and does not meet the use conditions of high temperature.

[0020] The specific technical scheme of a solvent-free polyurea coating and a preparation method and application thereof of the present invention is as follows:

[0021] A solvent-free polyurea coating, comprising component A and component B.

[0022] The raw material formula of the A component includes, by weight: 32.04 parts of polyaspartic acid ester resin, 2.12-3.92 parts of aminosilane resin, 3.64-3.89 parts of auxiliary agent and 8.5-12.3 parts of pigment;

[0023] The raw material formula of the B component includes, by weight: 22.24 or 22.70 parts of polyisocyanate, 5.3-10.2 parts of epoxy silicone resin, 2.6-2.79 parts of auxiliary agent, 6-8.5 parts of anti-rust pigment and 20.17-22 parts of filler;

[0024] The volume ratio of component A to component B is 1:1;

[0025] The solvent-free polyurea coating has a volume solid content of ≥99%.

[0026] Preferably, the polyaspartic acid ester resin in the A component includes a mixture of N,N'-(methylenebis-4,1-cyclohexylaminodiyl)bis-1,1',4,4'-tetraethyl ester and N,N'-[methylenebis(2-methyl-4,1-cyclohexylaminodiyl)]bis-1,1',4,4'-tetraethyl ester.

[0027] Preferably, the ratio of N,N'-(methylenebis-4,1-cyclohexylaminediyl)bis-1,1',4,4'-tetraethyl ester to N,N'-[methylenebis(2-methyl-4,1-cyclohexylaminediyl)]bis-1,1',4,4'-tetraethyl ester is 1-3:1.

[0028] Preferred are N,N'-(methylenebis-4,1-cyclohexylaminodiyl)bis-1,1',4,4'-tetraethyl ester and N,N'-[methylenebis(2-methyl-4,1-cyclohexylaminodiyl)]bis-1,1',4,4'-tetraethyl ester having a medium gelation rate.

[0029] Preferably, the aminosilane resin in component A includes 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane in conventional primary aminosilane resins, and bis[3-(triethoxysilyl)propyl]amine and bis(3-trimethoxysilylpropyl)amine in secondary aminosilane resins;

[0030] Preferably, the aminosilane resin is bis[3-(triethoxysilyl)propyl]amine or bis(3-trimethoxysilylpropyl)amine among the secondary aminosilane resins.

[0031] Most preferably, the aminosilane resin is a secondary aminosilane resin bis(3-trimethoxysilylpropyl)amine selected from Evonik Degussa 1124Bis(3-trimethoxysilylpropyl)amine.

[0032] Preferably, the pigment in component A is one or more of titanium dioxide, iron oxide pigment and carbon black.

[0033] Most preferably, the pigment is rutile titanium dioxide.

[0034] Preferably, the auxiliary agents in component A include thixotropic agents, dispersants, defoaming agents, leveling agents, light stabilizers and ultraviolet absorbers.

[0035] Preferably, the raw material formula of component A includes, by mass, 32.04 parts of polyaspartic acid ester resin, 2.12-3.92 parts of aminosilane resin, 8.5-12.3 parts of pigment, 0.2 parts of thixotropic agent, 0.2-0.35 parts of dispersant, 0.3 parts of defoaming agent, 0.64 parts of leveling agent, 0.8 parts of light stabilizer and 1.5-1.6 parts of ultraviolet absorber.

[0036] Preferably, the thixotropic agent is at least one of fumed silica, organic bentonite and polyamide wax.

[0037] Most preferably, the thixotropic agent is polyamide wax powder, selected from Luvotix VP031 of German Luvotix AG.

[0038] Preferably, the dispersant is a high molecular weight wetting dispersant.

[0039] Most preferably, the high molecular weight wetting and dispersing agent is selected from DISPERBYK-2155 produced by BYK.

[0040] Preferably, the defoamer is a silicone defoamer.

[0041] Most preferably, the defoamer is a polysiloxane defoamer with a foam breaking function and a hydrophobic particle silicone defoamer selected from BYK 1799, BYK 1796 and Evonik Airex 900.

[0042] Preferably, the leveling agent is an organic silicon surface additive selected from BYK 333 produced by BYK.

[0043] Preferably, the ultraviolet light absorber is a benzotriazole ultraviolet light absorber, selected from Eversorb 80 produced by Everlight in Taiwan Province, China.

[0044] Preferably, the light stabilizer is a hindered amine light stabilizer selected from Eversorb 93 produced by Everlight in Taiwan Province, China.

[0045] Preferably, the polyisocyanate in the B component is HDI (hexamethylene diisocyanate) trimer.

[0046] Preferably, the polyisocyanate is an HDI trimer selected from Desmodur N 3900 from Covestro and Tolonate from Vencorex. TM HDT-LV2, solvent-free.

[0047] Preferably, the epoxy silicone resin in the B component is an epoxy hybrid silicone resin.

[0048] Most preferably, the epoxy silicone resin is a hydrogenated bisphenol A epoxy resin modified silicone hybrid resin, selected from SILIKOPON EF of Evonik, and does not contain solvent.

[0049] Preferably, the anti-rust pigment in the B component is an inorganic anti-rust pigment.

[0050] Preferably, the inorganic anti-rust pigment includes one or more of orthophosphate, polyphosphate, phosphite, borate, zinc-modified aluminum tripolyphosphate, strontium-modified aluminum tripolyphosphate and modified orthophosphate.

[0051] Most preferably, the anti-rust pigment is a modified orthophosphate, more preferably zinc aluminum orthophosphate, selected from Heubach, Germany. ZPA.

[0052] Preferably, the filler in the B component is quartz powder.

[0053] Preferably, the auxiliary agents in the B component include a dewatering agent, a dispersant, a thixotropic agent, and a defoaming agent.

[0054] Preferably, the raw material formula of the B component includes, by mass, 22.24 or 22.70 parts of polyisocyanate, 5.3-10.2 parts of epoxy silicone resin, 0.1-0.3 parts of dewatering agent, 0.98 parts of dispersant, 0.53 parts of thixotropic agent, 0.98 parts of defoaming agent, 6-8.5 parts of anti-rust pigment and 20.17-22 parts of filler.

[0055] Preferably, the dehydrating agent is a monofunctional, highly reactive, low-viscosity isocyanate-4-methylisocyanate benzenesulfonyl ester, the structural formula of which is shown below:

[0056]

[0057] The dewatering agent is selected from Additive T from OMG Borchers GmbH.

[0058] Preferably, the dispersant is a modified polyether containing a high pigment affinity group.

[0059] Preferably, the dispersant is a wetting dispersant selected from Tego Dispers 655 produced by Evonik.

[0060] Preferably, the thixotropic agent is at least one of fumed silica, organic bentonite and polyamide wax.

[0061] More preferably, the thixotropic agent is fumed silica.

[0062] Most preferably, the thixotropic agent is hydrophobic fumed silica, selected from HDK H20 from Wacker.

[0063] Preferably, the defoamer is a non-silicon defoamer.

[0064] Preferably, the defoamer is a defoamer with a chemical composition of polyolefin, selected from BYK-1790 produced by BYK.

[0065] The present invention provides a method for preparing a solvent-free polyurea coating, the preparation steps comprising:

[0066] S1. Drying of pigments and fillers: Dry the pigments and fillers at 120°C. After drying, the moisture content is controlled below 0.05% for use in components A and B.

[0067] S2. Preparation of component A: Add 60% of polyaspartic acid ester resin into a closed disperser, add aminosilane resin, dispersant, 50% of defoaming agent, pigment, and thixotropic agent during stirring, and disperse at high speed for 40 minutes at an online speed of 10m-15m / s. Take samples for testing the fineness to 50um to pass the dispersion; reduce the speed to 4m / s, add the remaining 40% of polyaspartic acid ester resin, 50% of defoaming agent, and leveling agent, ultraviolet light absorber, and light stabilizer, and continue to disperse at low speed for 20 minutes to obtain component A, which is sealed.

[0068] S3. Preparation of component B: Add 60% of polyisocyanate, epoxy silane resin, dewatering agent, filler, anti-rust pigment, thixotropic agent, dispersant and 50% of defoaming agent into a closed disperser, and disperse at high speed for 40 minutes at an online speed of 10m-15m / s. Take samples for testing the fineness to 50um, which is qualified; reduce the speed to 4m / s, add the remaining 40% of polyisocyanate and 50% of defoaming agent, and continue to disperse at low speed for 20 minutes to obtain component B, which is sealed and packaged.

[0069] S4. Preparation of solvent-free polyurea coating: Mix component A and component B in a volume ratio of 1:1.

[0070] The present invention also discloses an application of the solvent-free polyurea coating, wherein the solvent-free polyurea coating is applied to the outer surface of a steel pipe that has been shot blasted or sand blasted using a two-component airless spraying device to form an external protective coating.

[0071] Preferably, the steel pipe is a ductile iron pipe, and the solvent-free polyurea coating is coated on the outer surface of the ductile iron pipe, and the coating thickness of one spraying is ≥700um.

[0072] Preferably, the application of the solvent-free polyurea coating comprises the following steps:

[0073] S11. Sandblast or shot blast the outer wall of the steel pipe to make the roughness Rz ≥ 60μm;

[0074] S12, preheating the steel pipe to a temperature of 30°C-60°C;

[0075] S13, the steel pipe rotates at a certain speed, the speed is 36-40m / min;

[0076] S14, preheating components A and B to 40-50°C;

[0077] S15. Use two-component spraying equipment to transport component A and component B to the static mixer through independent feeding pipes in proportion. After mixing in the static mixer, they are transported to the spray gun connected to the static mixer. The spray gun atomizes the paint and sprays it on the pipe surface. The thickness of one spraying reaches more than 700um.

[0078] S16. After spraying, the pipe continues to rotate for 5 minutes to ensure that the paint is fully leveled and does not drip after stopping;

[0079] S17. After spraying, the steel pipe needs to be cured at a higher temperature in a drying room at a temperature of 40-60°C for 40 minutes.

[0080] S18. After the curing in the oven is completed, keep curing at room temperature for another 7 days before putting it into use.

[0081] The thixotropic polyamide wax powder in component A of the present invention is selected from Luvotix VP031 of German company Luvotix. Compared with common polyamide wax powder products, the biggest feature of this product is that it can achieve the same excellent thixotropic properties as polyamide wax powder. However, the activation of Luvotix VP031 does not require high processing temperature and long dispersion time as the activation of existing polyamide wax powder. It can be activated in a very short time under low temperature conditions.

[0082] The dispersant in component A is DISPERBYK-2155 from BYK. This dispersant is 100% solid / active ingredient, will not have a negative impact on the solid content of the solvent-free system, and will not accelerate the reaction in the two-component polyurethane system.

[0083] The defoamer in component A is selected from BYK 1799, BYK 1796 and Evonik Airex900, since the present invention is a solvent-free coating system, the system viscosity is relatively large, and a thick coating thickness is required in one coat, so higher requirements are placed on the defoaming ability of the system. The defoamer selected in the present invention is a highly efficient defoamer concentrate that can eliminate large bubbles and microbubbles, and is very suitable for high-solid content and high-viscosity application systems, and has a fast and efficient defoaming effect.

[0084] The leveling agent in component A is an organic silicon surface additive, which can reduce the occurrence of undesirable conditions such as dirt / whitening during the drying process of the polyurea coating, while reducing the surface tension of the system and improving the wetting ability. In the present invention, the leveling agent is selected from BYK 333 of BYK, which can greatly reduce the surface tension and improve the surface wetting of the solvent-free system to the substrate.

[0085] The ultraviolet light absorber in component A is a benzotriazole ultraviolet light absorber, preferably Eversorb 80 from Everlight in Taiwan Province, China. The function of the ultraviolet light absorber is to block and absorb ultraviolet rays, greatly reduce the radiation intensity to which the polymer material is subjected, prevent the polymer material from light degradation caused by long-term exposure to light sources, enhance weather resistance, and completely block ultraviolet rays.

[0086] The light stabilizer in component A is a hindered amine light stabilizer, preferably Eversorb 93 from Everlight in Taiwan Province, China. The light stabilizer can capture free radicals in the raw materials, block the chain reaction of light and oxygen aging, and prevent free radicals from continuously mechanically damaging the molecular chains. It effectively protects the polymer from yellowing, reduced gloss, and weakened physical properties caused by light and heat aging, and enhances the long-term weather resistance and stability of polymer products.

[0087] Mixing Eversorb 80 and Eversorb 93 has a better synergistic effect, which significantly improves the weather resistance of asparagine polyurea coating and has a good inhibitory effect on the reduction of coating gloss, cracks and discoloration.

[0088] In the present invention, since the polyurea coating is directly applied to the outer wall of the steel pipeline, in addition to providing an isolation barrier for the steel pipeline, it is also required to have excellent corrosion resistance. Therefore, an anti-rust pigment is added to the coating component B. The anti-rust pigment zinc aluminum orthophosphate is purchased from Heubach, Germany. ZPA, Zinc Aluminum Orthophosphate is a modified zinc phosphate anti-rust pigment that has a stronger ability to inhibit water solubility than ordinary zinc phosphate, thus forming a better anti-corrosion layer on the metal surface.

[0089] In the present invention, the filler of component B is quartz powder. The addition of quartz powder will further improve the wear resistance of the coating and has a positive effect on the impact wear of sand and stones on the ground pipelines in the desert areas of the Middle East.

[0090] The selection of pigments and fillers should not affect the weather resistance of the coating.

[0091] The dehydrating agent in component B is Additive T from OMG Borchers GmbH, which reacts with water faster than HDI and generates inert amides. This reaction can eliminate trace amounts of water in the system, thereby solving the problems caused by pigments, fillers, solvents and moisture in the preparation process of polyurea coatings, improving the storage stability of isocyanate curing agents, and avoiding viscosity increase and can swelling caused by moisture. At the same time, it can also solve the adverse phenomena caused by moisture in the construction environment, improve the loss of gloss and yellowing caused by moisture, and improve the bubble problem caused by the reaction of moisture with the curing agent component - NCO group.

[0092] The dispersant in component B is a modified polyether containing highly pigment-affinity groups, selected from Evonik's Tego Dispers655. This dispersant is 100% solid / active ingredient, will not have a negative impact on the solid content of the solvent-free system, and will not accelerate the reaction in the 2KPU system.

[0093] The solvent-free polyurea coating of the present invention has the following advantages:

[0094] 1. The present invention adds an aminosilane resin to the polyaspartic acid ester component, preliminarily crosslinks to obtain component A (aspartic acid ester component), adds an epoxysilane resin to the polyisocyanate component, preliminarily crosslinks to obtain component B (isocyanate curing agent component), and then fully mixes components A and B when used. After mixing, components A and B react rapidly and form a reaction system with each other to form a polyurea coating with a higher crosslinking density; at the same time, relatively more silane resins, including aminosilane resins and epoxysilane resins, can be introduced into the system. The silane resins can further improve the high temperature resistance, moisture and heat resistance, and corrosion resistance of the coating, and will not affect the weather resistance of the system. The coating has excellent light retention and weather resistance, and can meet the purpose of long-term use in hot areas in the Middle East.

[0095] 2. Aminosilane resin participates in the reaction system, which can provide curing agent for epoxy silane, ensure the cross-linking density of the system, and improve the mechanical properties of the coating. The addition of secondary aminosilane resin has no significant effect on the usable time and curing speed of the asparagine polyurea system; it can also be used as an adhesion promoter of the system to improve the adhesion to the substrate, increase the resin's compatibility with inorganic pigments and fillers, thereby improving the cohesion and strength of the coating, and at the same time enhancing the flexibility, corrosion resistance, and weather resistance of the coating; due to the low viscosity of this type of resin, in the A component with filler, it can significantly reduce the viscosity of the system, and can be used as an active diluent for solvent-free systems to improve construction properties.

[0096] 3. Epoxy silicone resin combines the advantages of silicone resin and epoxy resin. It has the heat resistance and water resistance of silicone compounds, and maintains the high bonding strength of epoxy resin. In addition, the hydrogenated bisphenol A epoxy resin modified silicone hybrid resin will not affect the weather resistance of the system, and has excellent gloss retention and weather resistance. The epoxy group can react with the aminosilane and aspartic acid ester of component A, has a high cross-linking density, can further improve the heat resistance of the coating, and has an adhesion-promoting effect, further improving the adhesion of the coating, so that the system has excellent corrosion resistance, which meets the purpose of long-term use in hot areas of the Middle East, and has hydrophobic and stain-resistant properties.

[0097] 4. The solvent-free polyurea coating provided by the present invention is a two-component coating, and the volume ratio of component A to component B is 1:1, which overcomes the defect of the current market that the ratio is not 1:1;

[0098] In the existing asparagine polyurea products or related disclosed technologies, the ratio difference of the two components is relatively large (for example, 3:1 or 1:3). Once the ratio of one component changes slightly, the ratio of the entire coating will change significantly, affecting the performance of the coating. The spraying equipment has a pressure difference during the spraying process, which is disadvantageous for coatings with a large ratio difference and easily leads to an imbalance in the coating ratio.

[0099] Polyurea coatings have higher requirements on the accuracy of coating proportions than other coatings (such as epoxy coatings). Therefore, the present invention provides a two-component solvent-free polyurea coating, a coating composition with a two-component volume ratio of 1:1, which is conducive to the precise control of the proportion during the spraying process and is also conducive to the matching of spraying equipment currently on the market.

[0100] 5. The coating has excellent high temperature resistance. In order to simulate the effect of ambient temperature changes in the Middle East on the coating, adhesion tests were conducted in high temperature environment, temperature alternating environment, and high temperature and ultraviolet light alternating environment. The coating still has excellent adhesion to steel pipes.

[0101] The tests are:

[0102] The pull-off adhesion at room temperature (23°C) can reach over 20Mpa;

[0103] High temperature adhesion test: 85℃ continuous baking for 8h, and the adhesion tested at this temperature can reach more than 16Mpa;

[0104] Simulated temperature alternation experiment: 85℃ continuous baking for 8h, then cooling to room temperature and keeping for 16h. This is one cycle. The experiment needs to be carried out for 6 months in total, and then the adhesion test is carried out. The adhesion can reach more than 16Mpa.

[0105] 6. The coating has excellent resistance to moisture and heat. The cured coated pipe is placed in a curing furnace at 95% humidity and 85°C for 24 hours, and then the adhesion is tested in this environment. The adhesion can reach more than 14Mpa.

[0106] 7. The coating has excellent weather resistance and aging resistance. In order to simulate the impact of high temperature and sunshine in the Middle East on the coating, it is baked at 85°C for 8 hours, and then subjected to ultraviolet accelerated aging for 16 hours in accordance with GB / T 1865. This process is a cycle, and a total of 6 months of experiments are required. After that, the adhesion test is carried out, and there is no decrease in adhesion.

[0107] 8. The coating has excellent corrosion resistance. When the cured coated pipe is placed in acidic, alkaline and neutral solutions, there are no bubbles, cracks or peeling on the coating.

[0108] 9. The solvent-free polyurea coating provided by the present invention does not contain solvents, and can achieve a one-time film thickness of 700um. It does not contain any organic solvents, is safe, environmentally friendly and hygienic, and meets the requirements of the GB 17219 / T domestic drinking water transmission and distribution equipment and protective materials safety evaluation standard, and can be used for the anti-corrosion inner coating of high-temperature drinking water transportation steel pipelines. DETAILED DESCRIPTION

[0109] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation method, structure, characteristics and effects of the present invention are described in detail below in combination with the preferred embodiments.

[0110] The application process of all embodiments of the present invention is as follows:

[0111] S11. Sandblast or shot blast the outer wall of the steel pipe to make the roughness Rz ≥ 60μm;

[0112] S12, preheating the steel pipe to a temperature of 30°C-60°C, which is conducive to removing moisture from the surface of the steel pipe and providing a basic temperature for curing of the coating;

[0113] S13, the steel pipe rotates at a certain speed, the speed is 36-40m / min, and the speed can be adjusted within the range according to the different pipe diameters and the size of the nozzle;

[0114] S14, preheating components A and B to a temperature of 40-50° C. The polyurea coating of the present invention is a solvent-free coating and has a high viscosity at room temperature, so preheating is required to reduce the viscosity;

[0115] S15. Use two-component spraying equipment to transport component A and component B to the static mixer through independent feeding pipes in proportion. After mixing in the static mixer, immediately transport them to the spray gun connected to the static mixer. The length of the feeding pipe connecting the spray gun and the static mixer cannot be greater than 0.3m. The spray gun atomizes the paint and sprays it on the pipe surface. The thickness of one spraying reaches more than 700um, which meets the requirements of EN 15189 standard. It is also possible to obtain a higher coating thickness by adjusting the thixotropy and curing speed.

[0116] S16. After spraying, the pipe continues to rotate for 5 minutes to make the paint fully level and not drip after stopping. Secondary spraying is not allowed, and then enter the curing process;

[0117] S17. After spraying, the steel pipe needs to be cured at a higher temperature in the drying room. The curing temperature is 40-60°C and the curing time is 40 minutes. After completion, it can be taken off the production line.

[0118] S18. After the curing in the oven is completed, keep curing at room temperature for 7 days, then carry out performance testing and put it into use.

[0119] It includes normal temperature test and the effect of environmental changes in the Middle East on the coating, high temperature adhesion test in high temperature environment, temperature alternating environment, high temperature and ultraviolet light alternating environment. Adhesion test is tested according to ASTM D4541 standard.

[0120] Normal temperature adhesion test: Tested at 25°C;

[0121] High temperature adhesion test: Bake at 85℃ for 8h and test the adhesion at this temperature.

[0122] Temperature alternation test: Bake at 85°C for 8 hours, then cool to room temperature and keep for 16 hours. This is one cycle. The experiment needs to be carried out for a total of 6 months, and then the adhesion test is carried out.

[0123] Moisture and heat resistance test: Place the test coated pipe in a curing furnace with a humidity of 95% and a temperature of 85°C for 24 hours, and then test the adhesion in this environment.

[0124] Weathering test: To simulate the effects of high temperature and sunshine in the Middle East on the coating, the coating was baked at 85°C for 8 hours, and then subjected to UV accelerated aging for 16 hours in accordance with GB / T 1865. This process is one cycle, and the experiment lasts for 6 months, followed by adhesion testing.

[0125] Abrasion resistance (ASTM D 4060): 1kg / 1000r, CS-17 wheel, observe coating loss.

[0126] The specific test process of wear resistance is tested according to ASTM D4060 standard.

[0127] Impact resistance (ASTM G14): After the impact test, the coating has no leakage phenomenon.

[0128] The specific test process of impact resistance is tested according to ASTM G14 standard.

[0129] Acid resistance: After soaking in 20% H2SO4 for 2 years, no blistering, cracking or peeling of the coating was observed.

[0130] Alkali resistance: After soaking in 25% NaOH for 2 years, the coating showed no blistering, cracking or peeling.

[0131] Distilled water resistance: After soaking in 50℃ distilled water for 2 years, the coating was observed to have no blistering, cracking or peeling.

[0132] Salt spray resistance: scratched, lasts for 1 year, and the coating scratch does not extend.

[0133] The specific test process of salt spray resistance is tested in accordance with GB / T 1771 standard.

[0134] Aging resistance: 1 year, no decrease in coating adhesion, no cracking of the coating and 3000h gloss retention rate.

[0135] The specific experimental process of aging resistance is tested in accordance with GB / T 1865 standard.

[0136] The specific test data are shown in Tables 1 and 2 below.

[0137] Example 1

[0138] S1. Drying of pigments and fillers: Dry rutile titanium dioxide, aluminum zinc orthophosphate and quartz powder at a temperature of 120° C. The moisture content after drying is controlled below 0.05% for use in components A and B.

[0139] S2. Preparation of component A: 19.22 parts of polyaspartic acid resin are added to a closed disperser. The polyaspartic acid resin is prepared by mixing 16.02 parts of N,N'-(methylenebis-4,1-cyclohexylaminediyl)bis-1,1',4,4'-tetraethyl ester and 16.02 parts of N,N'-[methylenebis(2-methyl-4,1-cyclohexylaminediyl)]bis-1,1',4,4'-tetraethyl ester in a ratio of 1:1. Add 2.12 parts of aminosilane resin, 0.2 parts of high molecular weight wetting and dispersing agent, 0.15 parts of silicone defoamer, 0.2 parts of polyamide wax powder (thixotropic agent), and 8.5 parts of rutile titanium dioxide during stirring, and disperse at high speed for 40 minutes at an online speed of 10 m / s. Take samples to test the fineness of 50 um to pass the dispersion; reduce the speed to 4 m / s, add the remaining 12.82 parts of polyaspartic acid ester resin, 0.15 parts of silicone defoamer, and 0.64 parts of silicone surface additive (leveling agent), 1.5 parts of benzotriazole ultraviolet light absorber and 0.8 parts of hindered amine light stabilizer, continue to disperse at low speed for 20 minutes, and obtain component A, which is sealed.

[0140] S3, preparation of component B: add 13.62 parts of HDI trimer, 5.3 parts of epoxy silane resin, 0.3 parts of isocyanate-4-methyl isocyanate benzenesulfonyl ester (dewatering agent), 20.17 parts of quartz powder, 8.5 parts of zinc aluminum orthophosphate, 0.53 parts of fumed silica (thixotropic agent), 0.98 parts of high molecular weight wetting dispersant and 0.49 parts of non-silicon defoaming agent into a closed disperser, and disperse at high speed for 40 minutes at an online speed of 10 m / s. Samples are taken for testing fineness to 50 um, which is qualified dispersion; reduce the speed to 4 m / s, add the remaining 9.08 parts of HDI trimer and 0.49 parts of non-silicon defoaming agent, and continue to disperse at low speed for 20 minutes to obtain component B, which is sealed and packaged.

[0141] S4. The components A and B obtained through the above preparation process are mixed into a solvent-free polyurea coating using a two-component airless spraying device, with the volume ratio of component A to component B being 1:1. The coating is sprayed on the outer surface of the shot-blasted ductile iron pipe to form an external protective coating.

[0142] Example 2

[0143] S1. Drying of pigments and fillers: Dry rutile titanium dioxide, aluminum zinc orthophosphate and quartz powder at a temperature of 120° C. The moisture content after drying is controlled below 0.05% for use in components A and B.

[0144] S2. Preparation of component A: 19.22 parts of polyaspartic acid resin are added to a closed disperser. The polyaspartic acid resin is prepared by mixing 24.03 parts of N,N'-(methylenebis-4,1-cyclohexylaminediyl)bis-1,1',4,4'-tetraethyl ester and 8.01 parts of N,N'-[methylenebis(2-methyl-4,1-cyclohexylaminediyl)]bis-1,1',4,4'-tetraethyl ester in a ratio of 3:1. Add 3.92 parts of aminosilane resin, 0.35 parts of high molecular weight wetting and dispersing agent, 0.15 parts of silicone defoamer, 0.2 parts of polyamide wax powder (thixotropic agent), and 11.7 parts of rutile titanium dioxide during stirring, and disperse at a high speed of 10 m / s for 40 minutes. Take samples to test the fineness of 50 um for qualified dispersion; reduce the speed to 4 m / s, add the remaining 12.82 parts of polyaspartic acid ester resin, 0.15 parts of silicone defoamer, and 0.64 parts of silicone surface additive (leveling agent), 1.6 parts of benzotriazole ultraviolet light absorber and 0.8 parts of hindered amine light stabilizer, continue to disperse at a low speed for 20 minutes, and obtain component A, which is sealed.

[0145] S3, preparation of component B: add 13.34 parts of HDI trimer, 10.2 parts of epoxy silane resin, 0.18 parts of isocyanate-4-methyl isocyanate benzenesulfonyl ester (dewatering agent), 20.17 parts of quartz powder, 6.0 parts of zinc aluminum orthophosphate, 0.53 parts of fumed silica (thixotropic agent), 0.98 parts of high molecular weight wetting dispersant and 0.49 parts of non-silicon defoaming agent into a closed disperser, and disperse at high speed for 40 minutes at an online speed of 10 m / s. Samples are taken for testing fineness to 50 um, which is qualified dispersion; reduce the speed to 4 m / s, add the remaining 8.9 parts of HDI trimer and 0.49 parts of non-silicon defoaming agent, and continue to disperse at low speed for 20 minutes to obtain component B, which is sealed and packaged.

[0146] S4. The components A and B obtained through the above preparation process are mixed into a solvent-free polyurea coating using a two-component airless spraying device, with the volume ratio of component A to component B being 1:1. The coating is sprayed on the outer surface of the shot-blasted ductile iron pipe to form an external protective coating.

[0147] Example 3

[0148] S1. Drying of pigments and fillers: Dry rutile titanium dioxide, aluminum zinc orthophosphate and quartz powder at a temperature of 120° C. The moisture content after drying is controlled below 0.05% for use in components A and B.

[0149] S2. Preparation of component A: 19.22 parts of polyaspartic acid resin are added to a closed disperser. The polyaspartic acid resin is prepared by mixing 21.47 parts of N,N'-(methylenebis-4,1-cyclohexylaminediyl)bis-1,1',4,4'-tetraethyl ester and 10.57 parts of N,N'-[methylenebis(2-methyl-4,1-cyclohexylaminediyl)]bis-1,1',4,4'-tetraethyl ester in a ratio of 2.03:1. Add 3.0 parts of aminosilane resin, 0.3 parts of high molecular weight wetting and dispersing agent, 0.15 parts of silicone defoamer, 0.2 parts of polyamide wax powder (thixotropic agent), and 12.3 parts of rutile titanium dioxide during stirring, and disperse at a high speed of 10 m / s for 40 minutes. Take samples to test the fineness of 50 um for qualified dispersion; reduce the speed to 4 m / s, add the remaining 12.82 parts of polyaspartic acid ester resin, 0.15 parts of silicone defoamer, and 0.64 parts of silicone surface additive (leveling agent), 1.6 parts of benzotriazole ultraviolet light absorber and 0.8 parts of hindered amine light stabilizer, continue to disperse at a low speed for 20 minutes, and obtain component A, which is sealed.

[0150] S3, preparation of component B: add 13.63 parts of HDI trimer, 7.8 parts of epoxy silane resin, 0.11 parts of isocyanate-4-methyl isocyanate benzenesulfonyl ester (dewatering agent), 22.0 parts of quartz powder, 6.0 parts of zinc aluminum orthophosphate, 0.53 parts of fumed silica (thixotropic agent), 0.98 parts of high molecular weight wetting dispersant and 0.49 parts of non-silicon defoaming agent into a closed disperser, and disperse at high speed for 40 minutes at an online speed of 10 m / s. Samples are taken for testing fineness to 50 um, which is qualified dispersion; reduce the speed to 4 m / s, add the remaining 9.09 parts of HDI trimer and 0.49 parts of non-silicon defoaming agent, and continue to disperse at low speed for 20 minutes to obtain component B, which is sealed and packaged.

[0151] S4. The components A and B obtained through the above preparation process are mixed into a solvent-free polyurea coating using a two-component airless spraying device, with the volume ratio of component A to component B being 1:1. The coating is sprayed on the outer surface of the shot-blasted ductile iron pipe to form an external protective coating.

[0152] Comparative Example 1

[0153] S1. Drying of pigments and fillers: Dry rutile titanium dioxide, aluminum zinc orthophosphate and quartz powder at a temperature of 120° C. The moisture content after drying is controlled below 0.05% for use in components A and B.

[0154] S2. Preparation of component A: 19.22 parts of polyaspartic acid resin are added to a closed disperser. The polyaspartic acid resin is prepared by mixing 24.03 parts of N,N'-(methylenebis-4,1-cyclohexylaminediyl)bis-1,1',4,4'-tetraethyl ester and 8.01 parts of N,N'-[methylenebis(2-methyl-4,1-cyclohexylaminediyl)]bis-1,1',4,4'-tetraethyl ester in a ratio of 3:1. Add 4.92 parts of aminosilane resin, 0.35 parts of high molecular weight wetting and dispersing agent, 0.15 parts of silicone defoamer, 0.2 parts of polyamide wax powder (thixotropic agent), and 11.7 parts of rutile titanium dioxide during stirring, and disperse at high speed for 40 minutes at an online speed of 10 m / s. Take samples to test the fineness of 50 um for qualified dispersion; reduce the speed to 4 m / s, add the remaining 12.82 parts of polyaspartic acid ester resin, 0.15 parts of silicone defoamer, and 0.64 parts of silicone surface additive (leveling agent), 1.6 parts of benzotriazole ultraviolet light absorber and 0.8 parts of hindered amine light stabilizer, continue to disperse at low speed for 20 minutes, and obtain component A, which is sealed.

[0155] S3, preparation of component B: add 13.34 parts of HDI trimer, 12.8 parts of epoxy silane resin, 0.18 parts of isocyanate-4-methyl isocyanate benzenesulfonyl ester (dewatering agent), 20.17 parts of quartz powder, 6.0 parts of zinc aluminum orthophosphate, 0.53 parts of fumed silica (thixotropic agent), 0.98 parts of high molecular weight wetting dispersant and 0.49 parts of non-silicon defoaming agent into a closed disperser, and disperse at high speed for 40 minutes at an online speed of 10 m / s. Samples are taken for testing fineness to 50 um, which is qualified dispersion; reduce the speed to 4 m / s, add the remaining 8.9 parts of HDI trimer and 0.49 parts of non-silicon defoaming agent, and continue to disperse at low speed for 20 minutes to obtain component B, which is sealed and packaged.

[0156] S4. The components A and B obtained through the above preparation process are mixed into a solvent-free polyurea coating using a two-component airless spraying device, with the volume ratio of component A to component B being 1:1. The coating is sprayed on the outer surface of the shot-blasted ductile iron pipe to form an external protective coating.

[0157] The raw material components of the coatings in Examples 1-3 and Comparative Example 1, the weight fractions of the raw materials and the test results are shown in Table 1:

[0158] Table 1

[0159]

[0160]

[0161]

[0162] In the table, the first row component of polyaspartic acid resin is N,N'-(methylenebis-4,1-cyclohexylaminodiyl)bis-1,1',4,4'-tetraethyl ester, and the second row component is N,N'-[methylenebis(2-methyl-4,1-cyclohexylaminodiyl)]bis-1,1',4,4'-tetraethyl ester.

[0163] In the above Examples 1-3, it is agreed that the amount of polyaspartic acid resin in component A is 32.04 parts, and the amount of polyisocyanate in component B that reacts therewith is obtained by calculation, and the amount of polyaspartic acid resin and the amount of polyisocyanate are added according to the reactive group equivalent ratio of 1:1-1.1.

[0164] According to Examples 1-3 and Comparative Example 1, when the content of the aminosilane resin is 2.12-3.92 parts and the content of the epoxy organic silane resin is 5.3-10.2 parts, the high temperature adhesion, temperature alternating test, weather resistance, and moisture and heat resistance of the coating show a tendency to increase with the increase in the amount of the silane resin; and when the content of the aminosilane resin in Comparative Example 1 is greater than 4 and the content of the epoxy organic silane resin is greater than 10.2, the adhesion of the temperature alternating test and the adhesion of the weather resistance of the coating are detected, and it is found that with the increase in the amount of the silane resin, the adhesion does not continue to increase, but there is an increase in the adhesion. At the same time, it can be found that the impact resistance of the material has also decreased. When the coating is impacted under the condition of an impact force of 7J and then a leakage test is performed, it is found that there is leakage, indicating that the coating has been damaged. This is because the addition of too much reactive silane will cause the coating to become more brittle and the cost to increase. Therefore, the present invention limits the content of aminosilane resin to between 2.12-3.92 parts, and the content of epoxy organic silane resin to between 5.3-10.2 parts, and the amount of aminosilane resin and epoxy organic silane resin is changed according to the reactive group equivalent ratio of 1:1.

[0165] Comparative Example 2

[0166] S1. Drying of pigments and fillers: Dry rutile titanium dioxide, aluminum zinc orthophosphate and quartz powder at a temperature of 120° C. The moisture content after drying is controlled below 0.05% for use in components A and B.

[0167] S2. Preparation of component A: 19.22 parts of polyaspartic acid resin are added to a closed disperser. The polyaspartic acid resin is prepared by mixing 16.02 parts of N,N'-(methylenebis-4,1-cyclohexylaminediyl)bis-1,1',4,4'-tetraethyl ester and 16.02 parts of N,N'-[methylenebis(2-methyl-4,1-cyclohexylaminediyl)]bis-1,1',4,4'-tetraethyl ester in a ratio of 1:1. Add 2.12 parts of aminosilane resin, 0.2 parts of high molecular weight wetting and dispersing agent, 0.15 parts of silicone defoamer, 0.2 parts of polyamide wax powder (thixotropic agent), and 8.5 parts of rutile titanium dioxide during stirring, and disperse at high speed for 40 minutes at an online speed of 10 m / s. Take samples to test the fineness of 50 um to pass the dispersion; reduce the speed to 4 m / s, add the remaining 12.82 parts of polyaspartic acid ester resin, 0.15 parts of silicone defoamer, and 0.64 parts of silicone surface additive (leveling agent), 1.5 parts of benzotriazole ultraviolet light absorber and 0.8 parts of hindered amine light stabilizer, continue to disperse at low speed for 20 minutes, and obtain component A, which is sealed.

[0168] S3, preparation of component B: add 13.62 parts of HDI trimer, 0.3 parts of isocyanate-4-methyl isocyanate benzenesulfonyl ester (dewatering agent), 20.17 parts of quartz powder, 8.5 parts of zinc aluminum orthophosphate, 0.53 parts of fumed silica (thixotropic agent), 0.98 parts of high molecular weight wetting dispersant and 0.49 parts of non-silicon defoaming agent into a closed disperser, and disperse at high speed for 40 minutes at an online speed of 10 m / s. Samples are taken for testing fineness to 50 um, which is qualified dispersion; reduce the speed to 4 m / s, add the remaining 9.08 parts of HDI trimer and 0.49 parts of non-silicon defoaming agent, and continue to disperse at low speed for 20 minutes to obtain component B, which is sealed and packaged.

[0169] S4. The components A and B obtained through the above preparation process are mixed into a solvent-free polyurea coating using a two-component airless spraying device, with the volume ratio of component A to component B being 1:1. The coating is sprayed on the outer surface of the shot-blasted ductile iron pipe to form an external protective coating.

[0170] Comparative Example 3

[0171] S1. Drying of pigments and fillers: Dry rutile titanium dioxide, aluminum zinc orthophosphate and quartz powder at a temperature of 120° C. The moisture content after drying is controlled below 0.05% for use in components A and B.

[0172] S2. Preparation of component A: 19.22 parts of polyaspartic acid resin are added to a closed disperser. The polyaspartic acid resin is prepared by mixing 16.02 parts of N,N'-(methylenebis-4,1-cyclohexylaminediyl)bis-1,1',4,4'-tetraethyl ester and 16.02 parts of N,N'-[methylenebis(2-methyl-4,1-cyclohexylaminediyl)]bis-1,1',4,4'-tetraethyl ester in a ratio of 1:1. Add 0.2 parts of high molecular weight wetting and dispersing agent, 0.15 parts of silicone defoaming agent, 0.2 parts of polyamide wax powder (thixotropic agent), and 8.5 parts of rutile titanium dioxide during stirring, and disperse at a high speed of 10 m / s for 40 minutes. Take samples to test the fineness of 50 um for qualified dispersion; reduce the speed to 4 m / s, add the remaining 12.82 parts of polyaspartic acid ester resin, 0.15 parts of silicone defoaming agent, and 0.64 parts of silicone surface additives (leveling agent), 1.5 parts of benzotriazole ultraviolet light absorber and 0.8 parts of hindered amine light stabilizer, continue to disperse at a low speed for 20 minutes, and obtain component A, which is sealed.

[0173] S3, preparation of component B: add 13.62 parts of HDI trimer, 5.3 parts of epoxy silane resin, 0.3 parts of isocyanate-4-methyl isocyanate benzenesulfonyl ester (dewatering agent), 20.17 parts of quartz powder, 8.5 parts of zinc aluminum orthophosphate, 0.53 parts of fumed silica (thixotropic agent), 0.98 parts of high molecular weight wetting dispersant and 0.49 parts of non-silicon defoaming agent into a closed disperser, and disperse at high speed for 40 minutes at an online speed of 10 m / s. Samples are taken for testing fineness to 50 um, which is qualified dispersion; reduce the speed to 4 m / s, add the remaining 9.08 parts of HDI trimer and 0.49 parts of non-silicon defoaming agent, and continue to disperse at low speed for 20 minutes to obtain component B, which is sealed and packaged.

[0174] S4. The components A and B obtained through the above preparation process are mixed into a solvent-free polyurea coating using a two-component airless spraying device, with the volume ratio of component A to component B being 1:1. The coating is sprayed on the outer surface of the shot-blasted ductile iron pipe to form an external protective coating.

[0175] Comparative Example 4

[0176] S1. Drying of pigments and fillers: Dry rutile titanium dioxide, aluminum zinc orthophosphate and quartz powder at a temperature of 120° C. The moisture content after drying is controlled below 0.05% for use in components A and B.

[0177] S2. Preparation of component A: Add 20.2 parts of polyaspartic acid resin into a closed disperser. The polyaspartic acid resin is prepared by mixing 17.65 parts of N,N'-(methylenebis-4,1-cyclohexylaminediyl)bis-1,1',4,4'-tetraethyl ester and 16.02 parts of N,N'-[methylenebis(2-methyl-4,1-cyclohexylaminediyl)]bis-1,1',4,4'-tetraethyl ester. Add 0.2 parts of high molecular weight wetting and dispersing agent, 0.15 parts of silicone defoaming agent, 0.2 parts of polyamide wax powder (thixotropic agent), and 8.5 parts of rutile titanium dioxide during stirring, and disperse at a high speed of 10 m / s for 40 minutes. Take samples to test the fineness of 50 um for qualified dispersion; reduce the speed to 4 m / s, add the remaining 13.47 parts of polyaspartic acid ester resin, 0.15 parts of silicone defoaming agent, and 0.64 parts of silicone surface additive (leveling agent), 1.5 parts of benzotriazole ultraviolet light absorber and 0.8 parts of hindered amine light stabilizer, continue to disperse at a low speed for 20 minutes, and obtain component A, which is sealed.

[0178] S3, preparation of component B: add 13.62 parts of HDI trimer, 5.3 parts of epoxy silane resin, 0.3 parts of isocyanate-4-methyl isocyanate benzenesulfonyl ester (dewatering agent), 20.17 parts of quartz powder, 8.5 parts of zinc aluminum orthophosphate, 0.53 parts of fumed silica (thixotropic agent), 0.98 parts of high molecular weight wetting dispersant and 0.49 parts of non-silicon defoaming agent into a closed disperser, and disperse at high speed for 40 minutes at an online speed of 10 m / s. Samples are taken for testing fineness to 50 um, which is qualified dispersion; reduce the speed to 4 m / s, add the remaining 9.08 parts of HDI trimer and 0.49 parts of non-silicon defoaming agent, and continue to disperse at low speed for 20 minutes to obtain component B, which is sealed and packaged.

[0179] S4. The components A and B obtained through the above preparation process are mixed into a solvent-free polyurea coating using a two-component airless spraying device, with the volume ratio of component A to component B being 1:1. The coating is sprayed on the outer surface of the shot-blasted ductile iron pipe to form an external protective coating.

[0180] Comparative Example 5

[0181] S1. Drying of pigments and fillers: Dry rutile titanium dioxide, aluminum zinc orthophosphate and quartz powder at a temperature of 120° C. The moisture content after drying is controlled below 0.05% for use in components A and B.

[0182] S2. Preparation of component A: 19.22 parts of polyaspartic acid resin are added to a closed disperser. The polyaspartic acid resin is prepared by mixing 16.02 parts of N,N'-(methylenebis-4,1-cyclohexylaminediyl)bis-1,1',4,4'-tetraethyl ester and 16.02 parts of N,N'-[methylenebis(2-methyl-4,1-cyclohexylaminediyl)]bis-1,1',4,4'-tetraethyl ester in a ratio of 1:1. Add 2.12 parts of aminosilane resin, 0.2 parts of high molecular weight wetting and dispersing agent, 0.15 parts of silicone defoamer, 0.2 parts of polyamide wax powder (thixotropic agent), and 8.5 parts of rutile titanium dioxide during stirring, and disperse at high speed for 40 minutes at an online speed of 10 m / s. Take samples to test the fineness of 50 um to pass the dispersion; reduce the speed to 4 m / s, add the remaining 12.82 parts of polyaspartic acid ester resin, 0.15 parts of silicone defoamer, and 0.64 parts of silicone surface additive (leveling agent), 1.5 parts of benzotriazole ultraviolet light absorber and 0.8 parts of hindered amine light stabilizer, continue to disperse at low speed for 20 minutes, and obtain component A, which is sealed.

[0183] S3, preparation of component B: add 14.28 parts of HDI trimer, 0.3 parts of isocyanate-4-methyl isocyanate benzenesulfonyl ester (dewatering agent), 20.17 parts of quartz powder, 8.5 parts of zinc aluminum orthophosphate, 0.53 parts of fumed silica (thixotropic agent), 0.98 parts of high molecular weight wetting dispersant and 0.49 parts of non-silicon defoaming agent into a closed disperser, and disperse at high speed for 40 minutes at an online speed of 10 m / s. Samples are taken for testing fineness to 50 um, which is qualified dispersion; reduce the speed to 4 m / s, add the remaining 9.52 parts of HDI trimer and 0.49 parts of non-silicon defoaming agent, and continue to disperse at low speed for 20 minutes to obtain component B, which is sealed and packaged.

[0184] S4. The components A and B obtained through the above preparation process are mixed into a solvent-free polyurea coating using a two-component airless spraying device, with the volume ratio of component A to component B being 1:1. The coating is sprayed on the outer surface of the shot-blasted ductile iron pipe to form an external protective coating.

[0185] Comparative Example 6

[0186] This comparative example is a coating prepared by the prior art. The main difference from the embodiment is that epoxy silane is added to component A. The type of material is similar to that of the embodiment, but individual raw materials are different from the types used in the present invention. The specific raw materials used and their weight percentages are shown in Table 2.

[0187] The raw material components and weight proportions of the raw materials and the test results of the coatings of Example 1 and Comparative Examples 2-6 are shown in Table 2:

[0188] Table 2

[0189]

[0190]

[0191]

[0192] Compared with Example 1, Comparative Example 2 differs only in that no epoxy silicone resin is added to component B, and the other components are the same as Example 1. With the addition of aminosilane resin, the room temperature adhesion is very good, which also shows that silane resin has the characteristic of improving adhesion. However, high temperature adhesion, temperature alternation test, weather resistance, and moisture and heat resistance all drop significantly, especially moisture and heat resistance. The coating becomes soft and blistering occurs. This is because the addition of aminosilane resin does not provide an epoxy curing agent to react with it, so the aminosilane resin competes with the reaction of polyaspartic acid resin and polyisocyanate, consumes part of the polyisocyanate, and there is unreacted polyaspartic acid resin in the coating, causing a decrease in crosslinking density, resulting in a serious decrease in coating performance. In addition, the excess polyaspartic acid resin continues to react with moisture in the air to generate carbon dioxide gas, forming air cushions between the layers of the coating and between the coating and the substrate, creating potential bubbling areas. Excessive polyaspartic acid resin on the coating surface reacts with moisture in the air, and the generated carbon dioxide escapes, making the coating surface rough, and forming lower-strength substituted urea floating on the coating surface, which is not conducive to weather resistance.

[0193] Compared with Example 1, Comparative Example 3 differs only in that aminosilane resin is not added to component A, and the other components are the same as Example 1. With the addition of epoxy silicone resin, the room temperature adhesion is very good, which shows that silane resin has the characteristic of improving adhesion. However, high temperature adhesion, temperature alternation test, weather resistance, and moisture and heat resistance all drop significantly, especially moisture and heat resistance. The coating becomes soft and bubbling occurs. This is because the addition of epoxy silicone resin does not provide an amino curing agent to react with it, so the epoxy silicone resin competes with the reaction of polyisocyanate and polyaspartic acid resin, consumes part of the polyaspartic acid resin, and there is unreacted polyisocyanate in the coating, resulting in a serious decline in coating performance.

[0194] Because the excessive polyisocyanate in component B cannot react fully, it exists in the form of mucus inside the coating, resulting in a decrease in coating strength, affecting coating performance, causing oily surface, and also causing coating bubbling.

[0195] Comparative Example 4 is different from Example 1 in that epoxy silicone resin is added to component B, and aminosilane resin is not added to component A. Considering that epoxy silicone resin will consume part of the polyaspartic acid resin in component A, more polyaspartic acid resin is added in an equivalent amount to react with it. The moisture and heat resistance of the coating is improved (no blistering), but the high temperature adhesion, temperature alternating test, and weather resistance are greatly reduced, and the moisture and heat resistance and other properties also fail to show satisfactory results.

[0196] Compared with Example 1, the difference between Comparative Example 5 is that aminosilane resin is added to component A, and epoxy silicone resin is not added to component B. Considering that the aminosilane resin will consume part of the polyisocyanate in component B, an equivalent amount of polyisocyanate is added to react with it. The moisture and heat resistance of the coating is improved (no blistering), but the high-temperature adhesion, temperature alternating test, and weather resistance are greatly reduced, and the moisture and heat resistance and other properties also fail to show satisfactory results.

[0197] Prior art comparative example 6 is a coating composition in which epoxysilane is added to component A. Since epoxyorganosilane reacts with polyaspartic acid ester, component A will consume part of the -NH group of polyaspartic acid ester during storage and stacking, and the -NCO group prepared in proportion with component B will not be able to react completely, resulting in a significant decrease in the high-temperature adhesion of the coating, the adhesion in the temperature alternating test, the adhesion in the temperature and ultraviolet alternating test, and the moisture and heat resistance adhesion, especially the moisture and heat resistance. The coating becomes soft and bubbling occurs, and at the same time, the viscosity of component A increases, which is not conducive to construction.

[0198] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A solvent-free polyurea coating, comprising component A and component B, characterized in that: The raw material formula of the A component includes, by weight: 32.04 parts of polyaspartic acid ester resin, 2.12-3.92 parts of aminosilane resin, 8.5-12.3 parts of pigment, 0.2 parts of thixotropic agent, 0.2-0.35 parts of dispersant, 0.3 parts of defoamer, 0.64 parts of leveling agent, 0.8 parts of light stabilizer and 1.5-1.6 parts of ultraviolet absorber; The raw material formula of the B component includes, by weight: 22.24 or 22.70 parts of polyisocyanate, 5.3-10.2 parts of epoxy silicone resin, 0.1-0.3 parts of dewatering agent, 0.98 parts of dispersant, 0.53 parts of thixotropic agent, 0.98 parts of defoaming agent, 6-8.5 parts of anti-rust pigment and 20.17-22 parts of filler; The polyaspartic acid ester resin in the A component includes a mixture of N,N'-(methylenebis-4,1-cyclohexylaminodiyl)bis-1,1',4,4'-tetraethyl ester and N,N'-[methylenebis(2-methyl-4,1-cyclohexylaminodiyl)]bis-1,1',4,4'-tetraethyl ester; The ratio of N,N'-(methylenebis-4,1-cyclohexylaminediyl)bis-1,1',4,4'-tetraethyl ester to N,N'-[methylenebis(2-methyl-4,1-cyclohexylaminediyl)]bis-1,1',4,4'-tetraethyl ester is 1-3:1; The aminosilane resin in the A component includes 3-aminopropyltriethoxysilane and 3-aminopropyltrimethoxysilane in the primary aminosilane resin, and bis[3-(triethoxysilyl)propyl]amine and bis(3-trimethoxysilylpropyl)amine in the secondary aminosilane resin; The epoxy silicone resin in the B component is a hydrogenated bisphenol A epoxy resin modified silicone hybrid resin; The volume ratio of component A to component B is 1:1; The solvent-free polyurea coating has a volume solid content of ≥99%.

2. The method for preparing the solvent-free polyurea coating according to claim 1, characterized in that: S1. Drying of pigments and fillers: Dry the pigments and fillers at a temperature of 120°C. After drying, the moisture content is controlled below 0.05% for use in components A and B. S2, preparation of component A: add 60% by weight of polyaspartic acid ester resin in a closed disperser, add aminosilane resin and additives during stirring, the additives include: dispersant, 50% by weight of defoamer, pigment, filler and thixotropic agent, disperse for 40 minutes, add the remaining 40% by weight of polyaspartic acid ester resin and additives, the additives include: 50% by weight of defoamer, leveling agent, ultraviolet light absorber and light stabilizer, disperse for 20 minutes, and obtain component A, which is sealed and packaged; S3, preparation of component B: add 60% by weight of polyisocyanate, epoxy silane resin, filler, anti-rust pigment and additives in a closed disperser, the additives include: dewatering agent, thixotropic agent, dispersant and 50% by weight of defoamer, disperse for 40 minutes, add the remaining 40% by weight of polyisocyanate and 50% by weight of defoamer and continue to disperse for 20 minutes to obtain component B, which is sealed and packaged; S4. Preparation of solvent-free polyurea coating: Mix component A and component B in a volume ratio of 1:

1.

3. The use of the solvent-free polyurea coating according to claim 1, characterized in that: The solvent-free polyurea coating is applied to the outer surface of the steel pipe that has been shot blasted or sand blasted by using a two-component airless spraying device to form an external protective coating.

4. The use of the solvent-free polyurea coating according to claim 3, characterized in that: The steel pipeline is a ductile iron pipe, and the solvent-free polyurea coating is coated on the outer surface of the ductile iron pipe, and the coating thickness of one spraying is ≥700um.

Citation Information

Patent Citations

  • Process for the preparation of coatings

    EP0403921A2

  • Protective coating having a bi-layer coating structure

    WO2002058569A1

  • Adhesion promoter for reactive polyurethanes

    WO2003054049A1

  • Two-component coating composition

    CN105008424A

  • Low-viscosity solvent-free polyurea coating as well as preparation method and application thereof

    CN113122129A